Complete genome sequence of “Candidatus Phytoplasma sacchari” obtained using a filter-based DNA enrichment method and Nanopore sequencing - Zhang, Rong-Yue; Wang, Xiao-Yan; Li, Jie; Shan, Hong-Li; Li, Yin-Hu; Huang, Ying-Kun; He, Xia-Hong (Frontiers in Microbiology, 2023)
Phytoplasmas are phloem-limited plant pathogens, such as sugarcane white leaf (SCWL) phytoplasma, which is responsible for heavy economic losses to the sugarcane industry. Characterization of phytoplasmas has been limited because they cannot be cultured in vitro. However, with the advent of genome sequencing, different aspects of phytoplasmas are being investigated. In this study, we developed a DNA enrichment method for sugarcane white leaf (SCWL) phytoplasma and evaluated the effect of DNA enrichment via Illumina sequencing technologies, utilized Illumina and Nanopore sequencing technologies to obtain the complete genome sequence of “Candidatus Phytoplasma sacchari” isolate SCWL1 that is associated with sugarcane white leaf in China. Illumina sequencing analysis elucidated that only 1.21% of the sequencing reads from total leaf DNA were mapped to the SCWL1 genome, whereas 40.97% of the sequencing reads from the enriched DNA were mapped to the SCWL1 genome. The genome of isolate SCWL1 consists of a 538,951 bp and 2976 bp long circular chromosome and a plasmid, respectively. We identified 459 protein-encoding genes, two complete 5S-23S-16S rRNA gene operons, 27 tRNA genes, and an incomplete potential mobile unit (PMU) in the circular chromosome. Phylogenetic analyses and average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) values based on the sequenced genome revealed that SCWL phytoplasma and sugarcane grassy shoot (SCGS) phytoplasma belonged to the same phytoplasma species. This study provides a genomic DNA enrichment method for phytoplasma sequencing. Moreover, we report the first complete genome of a “Ca. Phytoplasma sacchari” isolate, thus contributing to future studies on evolutionary relationship and pathogenic mechanisms of “Ca. Phytoplasma sacchari” isolates.